Building energy efficiency in japan: A benchmark for Malaysia in the development of renewable energy technology - Mansor, Hezil (2008)

(untitled)
Governments throughout the world, including Malaysia, began to look at diverse options in energy conservation and new energy resources, and energy efficiency technology. Malaysia ratifying the Kyoto Protocol in September 2003 has opened the way for Malaysian renewable energy project developers to seek financing under the Clean Development Mechanism. Another opportunity is emerging because Malaysia as one of the fastest growing building industries in the world, from which a corresponding increase in energy demand can be expected every years. Japan as a highly industrialized nation has faced serious pollution and two oil crises, and was obliged to bear environmental regulations and energy conservation measures over the short term. However, as result of the concerted efforts of the public and private sectors in response to the strict environmental and energy restrictions, Japan's energy efficiency has improved over the past 30 years and oil consumption has decreased even though the GDP has doubled. The objective of this paper is to discuss about existing energy efficiency technology in Japan and challenges, lessons, and current development of participation from public and private sectors toward clean energy policy by Japanese government, which can even be follow by the developing countries with some modifications. This study can contribute to our understanding on the applicability of the energy efficiency method in Japan, one of the countries that succeeded in adopting renewable energy in its national energy scenario, to become a benchmark to a country such as Malaysia.